(untitled) (Research, Society and Development, 2018)
The objective of this work is to present a survey of Scielo ’s national production in the last five years about the contributions of educational psychology to teacher education. The initial methodology used is bibliographic research. The descriptors used for the production survey were: Educational psychology, teacher training and internship in the Scielo database. As to the results, twenty-two productions were found in the database, which is characterized analytically for organizing in the following areas: ten productions are from the areas of human sciences, eight from natural sciences and four from mathematics. The productions found during the survey bring in their content citations to educational psychology and / or talk about pedagogical disciplines in general that deal with several aspects such as: student-teacher status, initial training, supervised internships and teaching practice, professional knowledge, the relationship theory and practice, improvement of teaching in teacher education, curricular internship, internship in high school, challenges of teaching. It is concluded after the verification of the materials produced that it is remarkable the importance of studying the themes that involve teacher training and in what ways the psychology have contributed to the exercise of training.